The cross border timber trade in Kalimantan: will stopping timber smugglers help solve the illegal logging problem in Indonesia? - Obidzinski, K.; Andrianto, A.; Wijaya, C.; Hernawan, D.; Belle, C.W. (Center for International Forestry Research, 2006)
Indonesian forestry officials, timber industry associations, NGOs and research institutions are of the opinion that timber smuggling is a key contributor to the illegal logging problem in Indonesia. It is often stated that international crime syndicates, run mainly from the neighboring countries (i.e. Malaysia), are responsible for timber smuggling activities. Other assumptions are that if Malaysia and Indonesia cooperated, smuggling could be eliminated, and if timber smuggling was stopped, the illegal logging problem in Indonesia would be under control. These are sweeping assumptions that so far have not been systematically analyzed. This study was aimed to look more comprehensively at the dynamics, extent, nature and modus operandi of timber smuggling between Indonesia and Malaysia in Kalimantan and to assess the claims that are being made about the significance of timber smuggling within the context of the illegal logging problem in Indonesia. The results of this study will be used to inform the on-going debates on this issue and contribute to possible corrective measures.